Effects of Self-Management Program for People with Over Body Mass Index and High Cholesterol in Chanthaburi: a Study of People at risk of Chronic Diseases in Tumbol Thachang, Chanthaburi Province, Thailand - นิธิรัตน์ พรฤดี; อร่ามศิลป์ ราตรี; ขาวแจ้ง จารุณี; ประจันโน วรรณศิริ; เล็กวงษ์ เสาวภา; อัมพันศิริรัตน์ อมาวสี (Journal of Health Science of Thailand, 2020)
This quasiexperimental study was to examine the effects of a self-management program. The samples were 30 people at-risk of chronic diseases in Thachang subdistrict, Chanthaburi, Thailand, equally divided into an experimental group and a comparison group. The experimental group was required to participate in a self-management program composed of 2 sessions: (1) 1-day health camp, and (2) 8 group meetings in 6 months; whereas, the comparison group participated in a 1-day health camp only. Weight, waistline, cholesterol, and intention to perform proper health behaviors of the samples were measured before and after program implementation. Statistics used for data analysis included paired t-test, t-test, Wilcoxon sign rank test, and Wilcoxon-Mann Whitney test. The results revealed that before program implementation, weight, waistline, cholesterol, and intention to perform proper health behaviors of the samples in both groups were not statistically different (p>0.05). After program implementation, weight, waistline, cholesterol of the samples in an experimental group were significantly lower; whereas, the intention to perform proper health behaviors was significantly higher than those before program implementation (p<0.05). In contrast, weight, cholesterol, and intention to perform proper health behaviors of the samples in a comparison group were not significantly different; and the waistline was higher than that before program implementation (p<0.05). Therefore, this self-management program was found to be effective and should be promoted to reduce risk factors among people at-risk of chronic diseases.